HAND PUPPET SHOW DEVELOPS LANGUAGE RECOGNITION AND EXPRESSIONS SKILLS FOR MENTALLY IMPAIRED CHILD - Kamkaew, Choladda; Makpa, Piyawadee; Saksiriphol, Daranee (Journal of Buddhist Anthropology, 2022)
The Objectives of this research article were to develop language recognition and expression skills with hand puppet theater activities of children with intellectual disabilities Minor level, aged between 6 - 8 years old and part of the thesis on Developing language perception and expression skills through hand puppet theater activities of children with intellectual disabilities low level, age between 6 - 8 years, sample population a child with intellectual disabilities Minor level, age between 6-8 years with IQ level 50 - 70, no redundant disabilities. Use a specific selection method. The research conducted consisted of the design of activities based on the following theoretical concepts: 1) the process of creating a puppet play 2) Theory of learning from models (Bandura) 3) 3R teaching theory for children with intellectual disabilities 4) Theories of learning from models (Bandura). SMCE Communication (Daid K.Berlo) The researcher designed the activities as follows: 1) Study the curriculum according to the Early Childhood Education Curriculum 2017, teaching methods, teaching and learning theory for children with intellectual disabilities; 3) Write a puppet show activity plan. 4) Bring the puppet theater activity plan to 3 experts to check the appropriateness of the content of the activity. It was found that the activity can be used. It consists of 3 steps, 10 minutes intro, 10 minutes in instruction, 10 minutes in summary, 24 sessions of the activity, 8 times a week, 3 times 40 minutes each, consisting of 1) personal information, 2) family information. and people around; 3) information about animals and animal voices; 4) language for communicating in daily life.